THE USE OF THE READ, ENCODE, ANNOTATE AND PONDER (REAP) STRATEGY TO IMPROVE STUDENTS’ READING COMPREHENSION - Syafina, Syafina; Aeni, Nur; Dollah, Syarifuddin (Universitas Negeri Makassar, 2022)
This study intends to determine whether or not the use of the REAP strategy is effective in improving students’ reading comprehension that focuses on literal and inferential level. The researcher used a pre-experimental design with one group for the pre-test and post-test and used the multiple-choice reading question as the instrument about narrative text for the pre-test, treatment, and post-test. The sample in this research was class IX.9 of SMP Negeri 9 Makassar. The findings from this study showed that the mean score of pre-tests was 60.89 and post-test was 76.07. This means that there was an increase in score after receiving treatment and based on the paired sample test the sig (2-tailed) is 0.00 < 0.05, it can be concluded that the use of read, encode, annotate and ponder (REAP) strategy is effective to improve students’ reading comprehension.